TEKNOLOGI PENGOLAHAN AIR GAMBUT ASIN MENJADI AIR SIAP MINUM DI KELURAHAN TANJUNG TENGAH, PENAJAM, KALIMANTAN TIMUR - Setiadi, Imam; Kristyawan, I Putu Angga (Jurnal Air Indonesia, 2015)
Low levels of clean water supply in the Tanjung Tengah village causing the high price of water. value of Fe and TDS in the village raw water is high. The value of Fe content is 388 mg/L and TDS value is 12930 mg / L. The installation of salty peat water treatment technology were done to overcome this problem. The Salty peat water treatment technology consists of coagulation flocculation system, clarifier, filtration, reverse osmosis and a distribution systems. Results showed that this treatment efficiency reaches 99%. Where the iron content of the treated water is less than 0.003 mg / L, with a TDS value down to be 77 mg / L. The treated water also meet drinking water quality standards.Ã‚Â Keywords : Clean Water, Salty Peat Water, Reverse Osmosis, Iron and TDS.